The model and the planning method of volume and variety assessment of innovative products in an industrial enterprise; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Anisimov V. G.; Anisimov E. G.; Saurenko T. N.; Sonkin M. A. Mikhail Arkadjevich (2017, 2017)
Title screen